Radar estimate of rainfall and latent heat release in tropical cyclones of the Bay of Bengal (MAUSAM, 1981)
Distribution of rainfall rates, and latent heat release in three tropical cyclones of the Ray of Bengal has been estimated with a coastal radar, It is shown that the latent heat release (LHR) distribution and its changes appear well related to the intensity changes of the system and will be a valuable input for storm modelling, Attention is drawn to an asymmetrical distribution of LHR in one storm and the need to postulate a mechanism for transfer of the energy released to the large scale storm field in such cases. The operational value of rainfall distribution estimates by radar for realtime warnings of flood and rain damage due to tropical cyclones is illustrated. Radar is the only available tool in this area for continuous monitoring of cyclones in the absence of a geostationary satellite, Even when the latter becomes available radar can provide the ground-truth for rainfall and latent heat release determinations.